2000
DOI: 10.1046/j.1365-2672.2000.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Shiga-toxin-producing Escherichia coli in faeces of healthy dairy cows, sheep and goats: prevalence and virulence properties

Abstract: Escherichia coli (STEC) in healthy dairy ruminants was investigated between 1996 and 1998 by a multiplex polymerase chain reaction (mPCR) technique. A total of 13 552 E. coli colonies from 726 cows, 28 sheep and 93 goats out of 112 randomly selected dairy farms in Hessia, Germany were analysed. STEC strains were recovered from 131 (18Á0%) cows, nine (32Á1%) sheep and 70 (75Á3%) goats. Further characterization of the STEC isolates showed that 89 (0Á66% of the investigated colonies) of animal ®eld strains carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
59
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 29 publications
21
59
3
Order By: Relevance
“…In different studies on STECs isolated from sheep and goats, this pathotype mostly do not carry stx2 and eae (28,(35)(36)(37)(38). Oliveira et al (32) reported lacking of eae gene among the STECs from ruminants which is almost in agreement with our observation in goats.…”
Section: Discussionsupporting
confidence: 83%
“…In different studies on STECs isolated from sheep and goats, this pathotype mostly do not carry stx2 and eae (28,(35)(36)(37)(38). Oliveira et al (32) reported lacking of eae gene among the STECs from ruminants which is almost in agreement with our observation in goats.…”
Section: Discussionsupporting
confidence: 83%
“…The frequency of the bacteria shedding in cattle is influenced by various factors (Dargatz et al, 1997;Hancock et al, 1997a,b;Cray et al, 1998). STEC shedding has also been demonstrated in small ruminants (Beutin et al, 1993(Beutin et al, , 1996aKudva et al, 1996;Zschock et al, 2000), and that may represent an equally serious risk for people as cattle infections as evidenced by a recent finding of STEC O157 in sheep milk in Supported by the Grant Agency of the Czech Republic (Grant No. 525/00/666).…”
mentioning
confidence: 99%
“…This contributes to diminishing the environmental pollution from manure disposal (11). However, animal manure is a well-known source of foodborne pathogenic bacteria (32,33,35,37,46,51,61,63,65), and its inappropriate use in vegetable crops, especially organic ones, contributes a risk to consumer health. Research data and regulations recommend evaluating and normalizing the use of animal manure at the agricultural production (20,21).…”
Section: Introductionmentioning
confidence: 99%